Sosialisasi Proctor Ujian Kompetensi Bahasa Jepang Internasional di SMA Kesatrian 2 Semarang - Tri Mulyani W; Budi Santoso; Sri Oemiati; Bayu Aryanto (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
As one of the requirements to work in Japan, mastery of the Japanese language is very important. The Japan government stipulates that foreign workers entering Japan must have Japan language skills. The JLPT (Noryokushiken) is a Japan Language Proficiency Test held in Japan and abroad to evaluate and certify the ability of non-native Japan speakers to speak Japan. In Indonesia, especially Semarang, the implementation of the JLPT Exam is coordinated by Dian Nuswantoro University and in collaboration with Kesatrian 2 High School as the location of the JLPT exam and involves Kesatrian High School teachers to be used as assistant exam supervisors. The requirement to become a proctor is to understand all the rules during the exam process. Because the teachers of Kesatrian 2 High School have never been assistant supervisors of the JLPT exam before, there is a need for socialization about the rules of the JLPT exam. With this socialization, the assistant supervisors can carry out their duties in accordance with the rules set by the Japan government.